The Effect of Foreign Ownership and Foreign Board Commissioners on Tax Avoidance - Eddy Suranta; Pratana Midiastuty; Hairani Ramayanti Hasibuan (Universitas Hayam Wuruk Perbanas, 2019)
This study aims to provide empirical evidence of the influence of foreign ownership and foreign board of commissioners on tax avoidance. The dependent variable is tax avoidance, measured using an effective tax rate proxy (ETR), and the independent variable is the structure of foreign ownership and foreign board of commissioners. It tested the theory of legitimacy using the sample consisting of 53 non-financial companies listed on the Indonesia Stock Exchange in 2012-2016. The results showed that the structure of foreign ownership has a positive effect on tax avoidance, where the greater the structure of foreign ownership, the higher the company to avoid tax. The results of the study do not support the legitimacy theory, explaining the role of foreign ownership in gaining legitimacy from the public by not doing tax avoidance. Furthermore, this study also proves that the proportion of foreign commissioners does not influence tax avoidance. The implication is that the government can encourage increased foreign ownership in order to optimize tax payment or to minimize tax avoidance.